Revisions of Corporate Law - Aoki, Hiroko (Zeitschrift für Japanisches Recht, 2001)
I. Introduction II. Development of Corporate Law 1. The First Period 2. The Second Period 3. The Third Period III. Achievement of the Year 2000: The New Law on Corporate Divisions (kaisha bunkatsu) 1. Overview 2. The New Law from the Viewpoint of the Practice. IV. Prospects for the Year 2001 1. Comprehensive Approach 2. Summary of the Proposal of April 2001